Cataract-specific posttranslational modifications and changes in the composition of urea-soluble protein fraction from the rat lens - Yanshole, Lyudmila V. (Molecular Vision, 2013)
PURPOSE: To determine age-related changes in the composition of the urea-soluble (US) protein fraction from lenses of senescence-accelerated OXYS (cataract model) and Wistar (control) rats and to establish posttranslational modifications (PTMs) occurring under enhanced oxidative stress in OXYS lenses. METHODS: The identity and the relative abundance of crystallins in the US fractions were determined using two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption ionization–time of flight mass spectrometry (MS). The identities and the positions of PTMs were established using MS/MS measurements. RESULTS: Two-dimensional gel electrophoresis maps of US protein fractions were obtained for lenses of 3-, 12-, and 62-week-old Wistar and OXYS rats, and the relative abundance of different isoforms of α-, β-, and γ-crystallins was determined. β-Crystallins were the major contributor of the US fraction in 3-week-old lenses (above 50%), γ-crystallins in 12-week-old lenses (50–60%), and in 62-week-old lenses, the contributions from all three crystallin families leveled out. The major interstrain difference was the elevated level of α-crystallins in the US fraction from 12-week-old OXYS lenses. Spots with increased relative abundance in OXYS maps were attributed to the cataract-specific spots of interest. The crystallins from these spots were subjected to MS/MS analysis, and the positions of acetylation, oxidation, deamidation, and phosphorylation were established. CONCLUSIONS: The increased relative abundance of α-crystallins in the US fraction from 12-week-old OXYS lenses points to the fast insolubilization of α-crystallins under oxidative stress. Most of the PTMs attributed to the cataract-specific modifications also correspond to α-crystallins. These PTMs include oxidation of methionine residues, deamidation of asparagine and glutamine residues, and phosphorylation of serine and threonine residues.